Criminalization of Consumers for Criticism Given to Companies Through Cyberspace in Theoretical Studies: Kriminalisasi Konsumen Atas Kritik yang Diberikan Kepada Perusahaan Melalui Dunia Maya dalam Kajian Teoritis - Putra, Tegar Islami; Fibrianti, Nurul (Annual Review of Legal Studies, 2024)
The rapid maneuvering of technology has an impact on the trade sector. Social media is one of the communication mediums that is not uncommon to be used as a means of evaluating a product. However, not all product assessments circulating in the community have a positive impact on the company to be used as a means of product review, there are consumers who make an assessment of a product on social media in a way that is not good, causing harm to the company's image. Whereas the limitation of opinion in Indonesia is a juridical matter. The purpose of this paper is to be able to provide an analysis of the criminalization of consumers for criticism given to companies with criticism given through social media. The research method used in this research is normative juridical research method, conducted by studying and examining the application of legal norms. This study found that in the application of consumer criminalization of criticism given to companies through cyberspace, it can be done if he has fulfilled the elements as stated in the legislation. However, not a few perpetrators are let off by judges for several reasons related to the weak consumer protection regulations in Indonesia. So in this case, it is important for judges to be able to pay attention to expert theories in making decisions, such as Speech Act Theory and Injuria Sine Damno Theory.